Are genes encoding proteoglycans really associated with the risk of anterior cruciate ligament rupture? - P Cięszczyk; K Willard; P Gronek; P Zmijewski; G Trybek; J Gronek; M Weber-Rajek; P Stastny; M Petr; E Lulińska-Kuklik; K Ficek; E Kemeryte-Riaubiene; et al. (Termedia Publishing House, 2017)
Proteoglycans are considered integral structural components of tendon and ligament and have been implicated in the resistance of compressive forces, collagen fibrillogenesis, matrix remodelling and cell signalling. Several sequence variants within genes encoding proteoglycans were recently implicated in modulating anterior cruciate ligament ruptures (ACLR). This study aimed to test the previously implicated variants in proteoglycan and vascular epithelial growth factor encoding genes with risk of ACLR in a population from Poland. A case control genetic association study was conducted using DNA samples from 143 healthy participants without a history of ACL injuries (99 male and 44 females) (CON group) and 229 surgically diagnosed ACLR participants (158 males and 71 females). All samples were genotyped for the ACAN: rs1516797, BGN: rs1042103, rs1126499, DCN: rs516115 and VEGFA: rs699947 variants. Main findings included the (i) ACAN rs1516797 G/T genotype which was underrepresented in the CON group (CON: 36%, n=52, ACLR: 49%, n=112, p=0.017, OR=1.68, 95% CI 1.09 to 2.57) when all participants were investigated and (ii) the BGN rs1042103 A allele was significantly under-represented in the male CON group compared to the male ACLR group (CON: 39%, n=78, ACLR: 49%, n=156, p=0.029, OR=1.5, 95% CI 1.05 to 2.15). Furthermore, BGN inferred haplotypes were highlighted with altered ACLR susceptibility. Although the study implicated the ACAN and BGN genes (combination of genotype, allele and haplotype) in modulating ACLR susceptibility, several differences were noted with previous published findings.